Relationship between Self Stigma and Expectations in Schizophrenic Patients - Muhammad Iqbal Martani; Iyus Yosep; Efri Widianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore the relationship between self-stigma and expectations in schizophrenic patients. The method used is scoping review with a descriptive approach. The results showed a significant relationship between self-stigma and expectations in schizophrenic patients. Negative self-stigma causes schizophrenic patients to lose self-confidence and low expectations while recovering from symptoms of schizophrenic patients. Low negative self-stigma leads to high levels of expectation in schizophrenic patients. So nurses have an essential role in reducing negative self-stigma in schizophrenic patients. In conclusion, there is a relationship between self-stigma and expectations in schizophrenic patients. Internal and external factors influence self-stigma. So support from the family is essential in building a positive self-stigma against schizophrenic patients. Keywords: Hope, Schizophrenia, Self-Stigma